2022
DOI: 10.1109/tits.2020.3032777
|View full text |Cite
|
Sign up to set email alerts
|

Displaying the Driving State of Automated Vehicles to Other Road Users: An International, Virtual Reality-Based Study as a First Step for the Harmonized Regulations of Novel Signaling Devices

Abstract: Additional signaling devices for highly automated vehicles (AVs) that can communicate their driving state to other road users can simplify the integration process in existing road traffic. This paper presents the results of an international, virtual reality-based study conducted in China, South Korea and the USA in which subjects assume the role of a pedestrian and are placed in direct encounter situations with an AV in a parking lot. A novel communication interface consisting of three displays is attached to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Besides, future AVs may have to detect explicit gestures of vulnerable road users for safety reasons (e.g., detection of an extended arm of cyclists [34,36]) and to comply with traffic rules (e.g., being responsive to signals used by traffic police [31][32][33]). Furthermore, as others [8,10,37] have shown as well, the present study demonstrated that an eHMI makes visible the invisible. at is, it may be hard for pedestrians to detect the initiation of deceleration of an approaching vehicle; an eHMI makes such information salient, thereby improving subjective clarity.…”
Section: Discussionsupporting
confidence: 89%
“…Besides, future AVs may have to detect explicit gestures of vulnerable road users for safety reasons (e.g., detection of an extended arm of cyclists [34,36]) and to comply with traffic rules (e.g., being responsive to signals used by traffic police [31][32][33]). Furthermore, as others [8,10,37] have shown as well, the present study demonstrated that an eHMI makes visible the invisible. at is, it may be hard for pedestrians to detect the initiation of deceleration of an approaching vehicle; an eHMI makes such information salient, thereby improving subjective clarity.…”
Section: Discussionsupporting
confidence: 89%
“…That is, participants tend to follow the eHMI's instructions, provided the message is unambiguous (De Clercq et al, 2019;Fridman et al, 2019). A recent experiment performed in a virtual parking garage concurs that eHMIs that communicate the car's upcoming deceleration contribute to a decrease in crossing time of pedestrians (Singer, Kobbert, Zandi, & Khanh, 2020).…”
Section: Introductionmentioning
confidence: 82%
“…An example of this is the current state of automation; that is, whether the automation is currently active or not. Another idea could be to have an eHMI of an automated car displaying when it is about to drive away a few seconds before the car will do so (Eisma et al, 2020;Singer et al, 2020). We see this type of anticipatory eHMIs as an interesting subject for follow-up research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mixed traffic situations, where automated and non-automated vehicles share the road, eHMIs can provide additional information, such as the driving state and intent, to other road users. In a VR simulator study, Singer et al (2020) explore a communication interface between the automated vehicle intending to park, and pedestrians. The user study results reveal that additional signals achieve a better perception of the vehicle's intention, and improve perceived safety.…”
Section: Discussionmentioning
confidence: 99%